(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The rapid evolution of digital technologies has significantly transformed consumer behavior, market structures, and regulatory approaches. In this context, metrology and standardization are acquiring new relevance in ensuring the protection of consumer rights. This article explores modern approaches to the role of metrology and standardization systems within the framework of digital transformation. It highlights key challenges, technological innovations, legal frameworks, and institutional reforms that shape consumer protection mechanisms in a digitalized economy. The study concludes with proposals to enhance trust, safety, and transparency in digital trade through modernized metrological and standardization practices.